Teacher mediation in L2 classroom task-based interaction. (June 2018) - Dao, Phung; Iwashita, Noriko
Abstract: Guided by the holistic view of the sociocultural theory towards learning and focusing on teacher assistance to learners' process of working through tasks, the current study investigated teacher task-related assistance and language mediation, and how language mediation is adjusted according to learner's responsivity in classroom interaction. Sixteen Chinese learners of English residing in Canada carried out meaning-focused tasks in an intact classroom, taught by an experienced teacher over a four-week period. Approximately 12 h of audio-recorded classroom interactions were transcribed and analysed qualitatively using microanalysis method to examine characteristics of teacher task-related and language mediation. The results indicate that the teacher provided both task-related assistance, which addressed different task issues (e.g., task clarification, modeling, eliciting, and direction), and language mediation that featured diverse characteristics and varying degree of collaboration, which led us to identify two levels of mediation: low and highly collaborative. These results are discussed in terms of the role of teacher task-related assistance and language mediation on assisting and mediating learner's appropriation of language form and process of working through tasks.